2012
DOI: 10.1002/jcb.24031
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative‐mechanical stress signals stem cell niche mediated Lrp5 osteogenesis in eNOS−/− null mice

Abstract: Introduction Calcific aortic valve disease(CAVD) is the most common indication for valve surgery in the USA. This study hypothesizes that calcific aortic valve disease develops secondary to Wnt3a/Lrp5 activation via oxidative-mechanical stress in eNOS null mice. Methods eNOS−/− mice were tested with experimental diets including a control (n=20), cholesterol (n=20), cholesterol + Atorvastatin (n=20). After 23 weeks the mice were tested for the development of aortic stenosis by Echo, Histology, MicroCT, and RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 40 publications
2
42
0
3
Order By: Relevance
“…Studies indicate that nitric oxide (NO) could modulate mineralisation and lower the expression of osteoblastic genes in vascular cells. In this regard, eNOS ‐/‐ mice under a cholesterol‐rich diet develop CAVD and mice with BAV have higher levels of Wnt3a, Lrp5 and Runx2 65. These data suggest that eNOS‐derived nitric oxide modulates the Wnt/Lrp5 pathway, which has been found to promote mineralisation of the aortic valve in patients with CAVD 18.…”
Section: Pathobiologymentioning
confidence: 88%
“…Studies indicate that nitric oxide (NO) could modulate mineralisation and lower the expression of osteoblastic genes in vascular cells. In this regard, eNOS ‐/‐ mice under a cholesterol‐rich diet develop CAVD and mice with BAV have higher levels of Wnt3a, Lrp5 and Runx2 65. These data suggest that eNOS‐derived nitric oxide modulates the Wnt/Lrp5 pathway, which has been found to promote mineralisation of the aortic valve in patients with CAVD 18.…”
Section: Pathobiologymentioning
confidence: 88%
“…[3][4][5] In this regard, various pathogenic processes such as lipid infiltration/retention, inflammation, and osteogenesis are now considered as key drivers of aortic valve mineralization. [6][7][8] A dysmetabolic state, characterized by insulin resistance/T2D, has been shown to play an important role in the development of aortic valve mineralization and the progression of AS.…”
mentioning
confidence: 99%
“…Alfieri et al (57) reported that in interstitial cells exposed to culture medium for ossification, Wnt3a provoked nuclear translocation of b-catenin and caused a change in the expression of ossification-related genes. Furthermore, oxidative stress causes AVICs to transform into osteoblasts via the Wnt3a/Lrg5 pathway (58). This demonstrates that downstream signaling may differ according to the type of stimulus for calcification and that we can expect drugs targeting calcification-related signaling to have various effects.…”
Section: Factors Involved In Calcificationmentioning
confidence: 99%